Altered kidney function induced by SARS-CoV-2 infection and acute kidney damage markers predict survival outcomes of COVID-19 patients: a prospective pilot study - Temiz, Mustafa Zafer; Hacibey, Ibrahim; Yazar, Ramazan Omer; Sevdi, Mehmet Salih; Kucuk, Suat Hayri; Alkurt, Gizem; Doganay, Levent; Dinler Doganay, Gizem; Dincer, Muhammet Murat; Yuruk, Emrah; Erkalp, Kerem; Muslumanoglu, Ahmet Yaser (Renal failure, 2022)
Literature with regard to coronavirus disease 2019 (COVID-19) associated morbidities and the risk factors for death are still emerging. In this study, we investigated the presence of kidney damage markers and their predictive value for survival among hospitalized subjects with COVID-19. Forty-seven participants was included and grouped as: 'COVID-19 patients before treatment', 'COVID-19 patients after treatment', 'COVID-19 patients under treatment in intensive care unit (ICU)', and 'controls'. Kidney function tests and several kidney injury biomarkers were compared between the groups. Cumulative rates of death from COVID-19 were determined using the Kaplan-Meier method. The associations between covariates including kidney injury markers and death from COVID-19 were examined, as well. Serum creatinine and cystatin C levels, urine Kidney Injury Molecule-1 (KIM-1)/creatinine ratio, and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI), CKD-EPI cystatin C, and CKD-EPI creatinine-cystatin C levels demonstrated significant difference among the groups. The most significant difference was noted between the groups 'COVID-19 patients before treatment' and 'COVID-19 patients under treatment in ICU'. Advancing age, proteinuria, elevated serum cystatin C, and urine KIM-1/creatinine ratio were all significant univariate correlates of death (p < 0.05, for all). However, only elevated urine KIM-1/creatinine ratio retained significance in an age, sex, and comorbidities adjusted multivariable Cox regression (OR 6.11; 95% CI: 1.22-30.53; p = 0.02), whereas serum cystatin C showing only a statistically non-significant trend (OR 1.42; 95% CI: 0.00-2.52; p = 0.09). Our findings clearly demonstrated the acute kidney injury related to COVID-19. Moreover, urine KIM-1/creatinine ratio was associated with COVID-19 specific death.